2021
DOI: 10.1002/jlb.3mir0321-156r
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in inflammation: Focus on the microRNA cargo of EVs in modulation of liver diseases

Abstract: Extracellular vesicles (EVs) are heterogeneous nanometer‐ranged particles that are released by cells under both normal and pathological conditions. EV cargo comprises of DNA, protein, lipids cargo, metabolites, mRNA, and non‐coding RNA that can modulate the immune system by altering inflammatory response. EV associated miRNAs contribute to the pathobiology of alcoholic liver disease, non‐alcoholic liver disease, viral hepatitis, acetaminophen‐induced liver injury, fibrosis, and hepatocellular carcinoma. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 157 publications
(205 reference statements)
0
15
0
Order By: Relevance
“…297 Overall, EVs are becoming valuable tools for detecting cell-to-cell and interorgan communication after alcohol exposure. 298 With further characterization, they will likely serve as essential diagnostic tools to characterize the varying pathologies that characterize the advancing stages in the spectrum of ALD. The scheme of EV-based interactions crucial for ALD development is presented in Figure 6.…”
Section: Extracellular Vesicles (Evs) As Diagnostic Toolsmentioning
confidence: 99%
“…297 Overall, EVs are becoming valuable tools for detecting cell-to-cell and interorgan communication after alcohol exposure. 298 With further characterization, they will likely serve as essential diagnostic tools to characterize the varying pathologies that characterize the advancing stages in the spectrum of ALD. The scheme of EV-based interactions crucial for ALD development is presented in Figure 6.…”
Section: Extracellular Vesicles (Evs) As Diagnostic Toolsmentioning
confidence: 99%
“…Total number of particles was evaluated from the cell free supernatant after miR-192 inhibition using Nanosight and presented as particles/ml (L). Heravi et al, 2015b;Hessvik and Llorente, 2018;Babuta et al, 2019;Babuta and Szabo, 2021). Majority of alcohol is metabolized in hepatocytes and alcohol metabolites induce oxidative stress (Momen-Heravi et al, 2015a).…”
Section: Mirna-192 Regulates the Exosome Secretion Via Targeting Rabs...mentioning
confidence: 99%
“…There are several factors such as RNA binding proteins (Ago2, hnRNPs and others), cellular stress, membrane proteins (such as neural sphingomyelinase 2) and the miRNA induced silencing complex (miRISC)-related pathway that affect the sorting of miRNA/cargoes into exosomes (Zhang et al, 2015;Fabbiano et al, 2020;Groot and Lee, 2020;Babuta and Szabo, 2021). The main components of miRISC include miRNA, miRNA-repressible mRNA, GW182, and Ago2 (Zhang et al, 2015;Babuta and Szabo, 2021), and we previously demonstrated that alcohol induces the expression of GW182 (Bukong et al, 2013). It is possible that alcohol is modulating the expression of these proteins to induce miRs sorting into exosomes.…”
Section: Mirna-192 Regulates the Exosome Secretion Via Targeting Rabs...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol promotes inflammation, steatosis, and subsequently fibrosis by regulating multiple miRNAs. [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] In alcohol-fed murine models, miR-132 and miR-155 levels were upregulated in Kupffer cells. 92 MiR-155 enhances the proinflammatory effects of alcohol on Kupffer cells.…”
Section: Dna Methylation Histone Modifications and Non-coding Rna In ...mentioning
confidence: 99%